2007
DOI: 10.1002/ijc.22571
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of 3,4‐dihydroxybenzoic acid on human gastric carcinoma cells involving JNK/p38 MAPK signaling activation

Abstract: 3,4-Dihydroxybenzoic acid (protocatechuic acid, PCA) is discussed to represent antioxidative food components in a human diet rich in fruits and vegetables, and has been shown to prevent carcinogenesis or antitumor growth in vivo. However, the molecular mechanisms involved in chemopreventive activity of PCA are poorly understood. In this study, investigations were conducted to examine the detailed signaling pathway involved in PCA-induced apoptosis in human gastric adenocarcinoma (AGS) cells. The data from cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 46 publications
5
73
0
3
Order By: Relevance
“…The Martin-Perez group demonstrated that this was due in part to activation of mitogen-activated protein kinases (MAPK) by lauryl gallate (2c) and, more particularly, the ERK1/2 kinases (Table 1) [29]. Protocatechuic acid (3) was capable of stimulating c-Jun N-terminal kinase (JNK), another p38 MAPK, and as a consequence induced cell death in HepG2 hepatocellular carcinoma and AGS human gastric adenocarcinoma cells (Table 1) [30,31]. Caffeic and ferulic derivatives (5, 6 and 7) target specifically the PKC protein kinase family and arrest growth of various cancer cells, such as for example U937 human leukemic cells (Table 1) [18,32,33].…”
Section: Group I: Polyphenolic Acids and Their Analoguesmentioning
confidence: 99%
“…The Martin-Perez group demonstrated that this was due in part to activation of mitogen-activated protein kinases (MAPK) by lauryl gallate (2c) and, more particularly, the ERK1/2 kinases (Table 1) [29]. Protocatechuic acid (3) was capable of stimulating c-Jun N-terminal kinase (JNK), another p38 MAPK, and as a consequence induced cell death in HepG2 hepatocellular carcinoma and AGS human gastric adenocarcinoma cells (Table 1) [30,31]. Caffeic and ferulic derivatives (5, 6 and 7) target specifically the PKC protein kinase family and arrest growth of various cancer cells, such as for example U937 human leukemic cells (Table 1) [18,32,33].…”
Section: Group I: Polyphenolic Acids and Their Analoguesmentioning
confidence: 99%
“…It is a main metabolite of complex polyphenols, especially anthocyanins, which are converted to PCA and also abundantly formed and absorbed in the large intestine because of microbial metabolization (Kay et al 2005, Vitaglione et al 2007. Previous reports of both in vitro and in vivo studies have demonstrated that PCA has anti-carcinogen (Tseng et al 2000, Yip et al 2006, Lin et al 2007), antihyperglycemia , Harini & Pugalendi 2010, antioxidant (Liu et al 2002, Sroka & Cisowski 2003, Masella et al 2004, Shi et al 2006, Tarozzi et al 2007, Chou et al 2010, Zhang et al 2011, and anti-inflammatory properties (Yan et al 2004, Min et al 2010, Wang et al 2010. However, no scientific investigation has yet been conducted on the effect of PCA on diabetes-induced cardiac dysfunction, which is also caused by oxidative stress, and thus this investigation was conducted to study the anti-hyperglycemic activity of PCA and the effect of PCA on diabetes-induced cardiac dysfunction and other related metabolic parameters in STZ-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…JNK activation is also regulated by scaffold proteins, JNKinteracting protein (JIP) and JNK stress-activated protein kinaseassociated protein 1 (JSAP1) (Whitmarsh et al, 1998;Ito et al, 1999). Depending on the cell type and the stimulus, JNK can activate a number of diverse downstream targets including members of the activator protein-1 (AP-1) family, c-Jun, JunD, activating transcriptional factor 2 (ATF2), Bcl-2 proteins, c-Myc and p53 (Bode and Dong, 2007;Lin et al, 2007). Whether JNK induces or suppresses apoptosis is largely dependent on the molecules it activates.…”
mentioning
confidence: 99%